1992
DOI: 10.3181/00379727-201-43503
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Secretion, Serum, and Cerebral Spinal Fluid Insulin and Insulin-Like Growth Factor-l Concentrations in Pigs with Streptozotocin-Induced Diabetes Mellitus

Abstract: Diabetes mellitus was induced using streptozotocin in five gilts between 8 and 12 weeks of age. Gilts were maintained with exogenous insulin (INS) except during experimental periods. Four litter-mate gilts served as controls. At 9 months of age, all gilts were ovariectomized, and 30 days after ovariectomy, Experiment (Exp) 1 was conducted. Jugular vein catheters were inserted and blood samples were collected every 10 min for 8 hr. Experiment 2 was conducted when gilts were 11 months of age. Venous blood and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The minipig has lower fasting plasma levels, compared with humans, for both insulin (Eriksson et al 1989;Faber et al 1978;Fritsche et al 2000;Larsen et al 2001Larsen et al , 2002cMatthews et al 1983;Reaven et al 1976), C-peptide (Faber et al 1978;Larsen et al 2001Larsen et al , 2002c, and glucose (Canavan et al 1997;Ellegaard et al 1995;Eriksson et al 1989;Matthews et al 1983;Fritsche et al 2000;Larsen et al 2001Larsen et al , 2002cReaven et al 1976;Weyer et al 1999), whereas domestic pigs have fasting glucose levels in the same range as in humans (Barb et al 1992;Ramsay and White 2000;Wilson et al 1986). Plasma levels of glucose and insulin increase with age both in minipigs ) and humans (Rosenthal et al 1982), indicating reduced insulin sensitivity and/or beta-cell function (Matthews et al 1985).…”
Section: Metabolism and Glucose Tolerancementioning
confidence: 86%
See 3 more Smart Citations
“…The minipig has lower fasting plasma levels, compared with humans, for both insulin (Eriksson et al 1989;Faber et al 1978;Fritsche et al 2000;Larsen et al 2001Larsen et al , 2002cMatthews et al 1983;Reaven et al 1976), C-peptide (Faber et al 1978;Larsen et al 2001Larsen et al , 2002c, and glucose (Canavan et al 1997;Ellegaard et al 1995;Eriksson et al 1989;Matthews et al 1983;Fritsche et al 2000;Larsen et al 2001Larsen et al , 2002cReaven et al 1976;Weyer et al 1999), whereas domestic pigs have fasting glucose levels in the same range as in humans (Barb et al 1992;Ramsay and White 2000;Wilson et al 1986). Plasma levels of glucose and insulin increase with age both in minipigs ) and humans (Rosenthal et al 1982), indicating reduced insulin sensitivity and/or beta-cell function (Matthews et al 1985).…”
Section: Metabolism and Glucose Tolerancementioning
confidence: 86%
“…Doses of 100 to 150 mg/kg of STZ have been reported to induce insulin-dependent diabetes in both domestic and minipigs in several studies (Barb et al 1992;Canavan et al 1997;Gabel et al 1985;Grussner et al 1993;Larsen et al 2002c;Wilson et al 1986). One study has reported that 150 mg/kg of STZ failed to induce diabetes in 7-to 8-mo-old Göttingen minipigs, whereas 200 mg/kg resulted in insulin-dependent diabetes ).…”
Section: Chemical Induction Of Diabetesmentioning
confidence: 93%
See 2 more Smart Citations
“…It circulates in blood bound to specific binding proteins (IGFBP) of approximately 18 and 43 kDa (Smith, 1984). IGF-I and IGFBPs in serum have been studied in gilts and sows under various experimental conditions including ovariectomy (Barb et al, 1992;Howard and Ford, 1992;Killen et al, 1992;Cox et al, 1994;Klindt et al, 1994). In boars, castration led to a fall in serum GH and IGF-I levels (Arbona et al, 1989;Dubreuil et al, 1989;Louveau et al, 1991).…”
mentioning
confidence: 99%